The role of anti-inflammatory diets and supplementation in metabolic syndrome and symptom remission in adults with schizophrenia: a systematic review - Elizabeth Suschana; Thea Anderson; Catriona Hong; Arun Narikatte; Jillian Silverberg; Manu Suresh Sharma (Frontiers in Psychiatry)
IntroductionImmune dysregulation and chronic inflammation have been hypothesized as potential pathways in metabolic syndrome and schizophrenia. Anti-inflammatory diets have the potential not only to treat metabolic syndrome but also to reduce the symptom burden in schizophrenia. The aim of this systematic review was to investigate the role of anti-inflammatory diets and vitamin supplementation in the management of metabolic syndrome and in symptom remission in people with schizophrenia.MethodsThis systematic review included research articles from PubMed, EMBASE, Scopus, PsycINFO, and the Cochrane Central Register for Controlled Trials. The primary outcomes were markers of metabolic syndrome and symptoms of psychosis.ResultsOur search identified 2,124 potential studies, of which 1,559 were screened based on the title and abstract, resulting in 81 full-text articles assessed for eligibility. A total of 17 studies were included, which demonstrated mixed findings on the impacts of anti-inflammatory diet interventions on metabolic markers and symptom remission in schizophrenia. Prebiotic, probiotic, and fish oil supplementation showed improvements in metabolic markers. Fish oil and vitamin D supplementation demonstrated symptom remission in some trials.ConclusionIt is important to consider that people with schizophrenia may experience common external barriers that hinder adherence to dietary interventions. These findings underscore the need for larger trials with standardized dietary protocols and consistent metabolic and symptom outcome measures in order to better understand the potential role of anti-inflammatory interventions in this population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024511596.